Enamel hypoplasia and dental wear of North American late Pleistocene horses and bison: an assessment of nutritionally based extinction models. Issue 3 (3rd June 2019) - Barrón-Ortiz, Christina I.; Jass, Christopher N.; Barrón-Corvera, Raúl; Austen, Jennifer; Theodor, Jessica M.
Abstract: Approximately 50, 000–11, 000 years ago many species around the world became extinct or were extirpated at a continental scale. The causes of the late Pleistocene extinctions have been extensively debated and continue to be poorly understood. Several extinction models have been proposed, including two nutritionally based extinction models: the coevolutionary disequilibrium and mosaic-nutrient models. These models draw upon the individualistic response of plant species to climate change to present a plausible scenario in which nutritional stress is considered one of the primary causes for the late Pleistocene extinctions. In this study, we tested predictions of the coevolutionary disequilibrium and mosaic-nutrient extinction models through the study of dental wear and enamel hypoplasia of Equus and Bison from various North American localities. The analysis of the dental wear (microwear and mesowear) of the samples yielded results that are consistent with predictions established for the coevolutionary disequilibrium model, but not for the mosaic-nutrient model. These ungulate species show statistically different dental wear patterns (suggesting dietary resource partitioning) during preglacial and full-glacial time intervals, but not during the postglacial in accordance with predictions of the coevolutionary disequilibrium model. In addition to changes in diet, these ungulates, specifically the equid species, show increased levels of enamel hypoplasia during the postglacial, indicating higher levels of systemic stress, a result that is consistent with the models tested and with other climate-based extinction models. The extent to which the increase in systemic stress was detrimental to equid populations remains to be further investigated, but suggests that environmental changes during the late Pleistocene significantly impacted North American equids.